Size structure of broadnose sevengill sharks (Notorynchus cepedianus) in Sawdust Bay, Rakiura/Stewart Island, estimated using underwater stereo-photogrammetry. Issue 1 (2nd January 2023) - Lewis, Robert; Dawson, Steve; Rayment, Will
ABSTRACT: The broadnose sevengill shark ( Notorynchus cepedianus ) is a large marine predator found in temperate coastal marine habitats. Despite being commonly encountered, details of its ecology are limited. To partially address this, we quantified the size and sex structure of N. cepedianus in Paterson Inlet, Stewart Island, New Zealand. A stereo-camera baited underwater video system (BRUV) was deployed in a shallow coastal embayment to capture underwater video of N. cepedianus for stereo photogrammetric measurement between June 2016 and November 2017. Individual sharks were sexed via observation of claspers. Three-dimensional underwater calibration of the photogrammetric system, using a precisely measured cube, indicated a mean error of <1%. Estimated total lengths ranged from 149.0 to 276.5 cm ( n = 78 individuals, mean = 211.4, S.E. = 2.97). The observed sex ratio was heavily biased, with females making up 95% of the population in winter 2016 and 73% in summer 2017. This study provides new data on N. cepedianus in southern New Zealand as well a non-invasive, low-cost methodology that can be applied to other study areas.